Roman Law and Riots on a Religious Background. The Example of Constitutions Preserved in “Codex Theodosianus 16.4. De His, Qui Super Religione Contendunt” - Świętoń, Adam (Studia Warmińskie, 2019)
The author discusses four imperial constitutions preserved in the fourth title of sixteenth book of Theodosian Code. The title is aimed at religious disputes. Controversies on the Christian doctrine in fourth century often turned into riots that were dangerous for the public order. Conflicts on the religious background interfered with tensions caused by social, economic and political changes. In the internal policy of the late Roman empire the concept of uniformity of the religious system appears as one of the requirements for the stable functioning of the state. Before publication of the Code in the year of 438, the emperor's constitutions included in the discussed title were issued in connection with specific cases of unrests caused by religious disputes. The original purpose of their promulgation was to restore public order and to fight heresy. However, the composition of the title De his, qui super religione contendunt raises question about its purpose. It can be considered whether, after 438 AD, it was restricted or completely prohibited to make any religious disputes without the approval of the emperor.